Between a rock and a hard place: the constitutional role of the Attorney-General in Sri Lanka. Issue 3 (2nd September 2022) - Dias, Sanjit
ABSTRACT: The Attorney-General of Sri Lanka makes representations to the Supreme Court in fundamental rights applications. The constitution envisions the Attorney-General acting independently and impartially in this regard, in the character of an "institution protecting democracy" within a "guarantor branch". However, the Attorney-General typically defends the respondents in all such fundamental rights cases. This is particularly true under article 35 of the constitution, where fundamental rights applications challenging official acts of the President must be instituted against the Attorney-General. This provision has long been interpreted as requiring the Attorney-General to defend these actions. A close examination of the whole constitutional scheme reveals, however, that no such requirement exists, and the Attorney-General has discretion on whether or not to defend any such action instituted against him. Adopting this approach would promote constitutional compliance by the executive branch, and has the potential to transform the landscape of constitutional practice in Sri Lanka.